The exopolyhedral ligand orientation (ELO) in 3‐(nitrato‐κO)‐3, 3‐bis(triphenylphosphane‐κP)‐3‐rhoda‐1, 2‐dicarba‐closo‐dodecaborane(11) dichloromethane 2.2‐solvate. Issue 6 (12th May 2015) - Rosair, Georgina M.; Scott, Greig; Welch, Alan J.
<x xml:space="preserve">Abstract</x> In the title compound, [Rh(C2H11B9)(NO3)(C18H15P)2]·2.2CH2Cl2, studied as a 2.2‐solvate of what was assumed to be dichloromethane, the nitrate ligand lies cis with respect to both cage C atoms. Accordingly, the compound displays a pronounced preferred exopolyhedral ligand orientation (ELO) which is traced to both the greater trans influence of the cage B over the cage C atoms and the greater trans influence of the triphenylphosphane ligands over the nitrate ligand. The overall molecular architecture therefore agrees with that of a number of similar 3‐L‐3, 3‐L′2‐3, 1, 2‐closo‐MC2B9H11 species in the literature.